Caracterização do papel do miRNA let-7a-5p no controle da resposta imune e inflamatória na hanseníase - Marina Pimenta Braga (2023)
Leprosy is a chronic and contagious infectious disease, whose etiological agent is Mycobacterium leprae. Currently, it is a disease that, despite having made great progress in reducing its transmission, still affects a considerably large number of people. It is characterized by a wide clinical spectrum that varies between the form of resistance (tuberculoid -TT) and the form of susceptibility (virchowian -VV), which manifest in different profiles of immune response. The control of the immune response involves a myriad of cellular and tissue processes and, among them, the control of gene expression is an essential factor. Previous results demonstrate that there is an important role for miRNAs, small non-coding RNAs, in the polar forms of leprosy. Previously, we identified the differential expression profile of miRNAs in patients with the polar forms of leprosy (TT and VV) and non-ill control subjects, and these profiles were used to identify, in silico, enriched cellular pathways that could be related to the pathophysiology of the disease. Among these pathways, the recognition pathways of pathogens or PAMPs stand out, such as signaling mediated by TLR4 (Toll-like receptor 4). This pathway has a central regulator, let-7a-5p, which targets the TLR4 receptor itself and is differentially expressed in the clinical forms of the disease. In this sense, considering that let-7a-5p may play an important role in regulating the recognition of the pathogen by TLR4, in the polar clinical forms of leprosy, the objective of this work was to characterize the function of the miRNA let- 7a-5p in the signaling control cell mediated by TLR4 and correlate with the pathophysiology of leprosy. For this purpose, in vitro systems were standardized in HEK293T and L929 cell cultures. The results demonstrate that TLR4 is a miRNA target and may have its expression controlled, at least in part, by let-7a-5p. Furthermore, the presence of the let-7a-5 mimic is capable of partially inhibiting the increase in CXCL1 after stimulating L929 fibroblasts with LPS, and we also observed changes in miRNA expression after stimulating cells with LPS and TLR4 mRNA alteration in cells treated with the miRNA mimic. The results generated in this work demonstrate that let-7a-5p is a controller of the TLR4-mediated inflammatory response in leprosy.